POSTCARD MOBILITY: going beyond image and text - Mavric, Misela; Andriotis, Konstantinos (My University, 2013)
Most existing research about postcards focuses merely on their visual representation, but postcards offer more than only images and texts. We analyse 134 postcards sent from Smyrna between 1895 and 1922 by discussing five interdependent mobilities constituting the New Mobilities Paradigm (Urry, 2000, 2007), namely mobility of objects, corporeal, imaginative, communicative and virtual mobility, and pertaining systems enabling them. We aim to show the empirical richness of postcards and a way of looking at them through the concept of mobilities. By this we uncover who were the people sending postcards, for what purposes, which places postcards connected through images and words, and how did postcards function as ordering artefacts in the pre-telephone and internet era
Keywords: Communication; Postcards; Internet; Tourism; Tourism--Research